2011
DOI: 10.1021/jp205244m
|View full text |Cite
|
Sign up to set email alerts
|

DFT-Based Study on Oxygen Adsorption on Defective Graphene-Supported Pt Nanoparticles

Abstract: The structural and electronic properties of Pt13 nanoparticles adsorbed on monovacancy defective graphene have been determined to understand oxygen adsorption on Pt nanoparticles based upon density functional theory predictions using the generalized gradient approximation. We demonstrate that a monovacancy site of graphene serves a key role as an anchoring point for Pt13 nanoparticles, ensuring their stability on defective graphene surfaces and suggesting their enhanced catalytic activity toward the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
178
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(193 citation statements)
references
References 56 publications
13
178
0
2
Order By: Relevance
“…The isolated Pt 13 13 -defective graphene are discussed in our previous study. 15 Fully relaxed and optimized Pt 13 -defective graphene systems were partially frozen for this ORR study to save computational effort. The boundary 83 carbon atoms out of 127 carbon atoms of defective graphene were frozen based on its negligible influence on O 2 adsorption and geometry change as shown in Supporting Information, Computational Methodology section 2 ( Figure S1 and Figure S2).…”
Section: Computational Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The isolated Pt 13 13 -defective graphene are discussed in our previous study. 15 Fully relaxed and optimized Pt 13 -defective graphene systems were partially frozen for this ORR study to save computational effort. The boundary 83 carbon atoms out of 127 carbon atoms of defective graphene were frozen based on its negligible influence on O 2 adsorption and geometry change as shown in Supporting Information, Computational Methodology section 2 ( Figure S1 and Figure S2).…”
Section: Computational Methodologymentioning
confidence: 99%
“…Furthermore, the vacancy sites in graphene can serve as anchoring points for the growth of nanoparticles. 14,15 Defective graphene-supported nanoparticles may enhance surface reactivity 14,16 and previous experimental studies have shown that atomic defects in graphene may be formed after several tens of seconds of irradiation with an electron beam 17 or by treatment with hydrochloric acid. 18 The mechanisms of the ORR have been investigated experimentally and theoretically for Pt and Pt alloy catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…12 and a trigonal pyramid by Ref. 13 Only the following larger-size clusters have been investigated: Pd-Au with n = 7; 137 Co, 138 Pt, 14 Fe, Co, Ni, 16 and MPd 12 (M = Fe, Co, Ni, Cu, Zn, Pd),, 15 and Au 49 . 139 These limitations, complexity, and controversies call for systematic study of TM n clusters on Gr sheet, to identify trends and classify the interactions between TM clusters and Gr.…”
Section: Graphenementioning
confidence: 99%
“…37 Even though, many theoretical studies have been conducted to describes the geometrical and eletronic properties of (TM) clusters on Gr support, they agree and disagree on many points. [8][9][10][11][12][13][14][15][16] To our knowledge, the dependence of structural and adsorption properties on cluster size has never been systematically studied from a theoretical perspective. These limitations, complexity, and controversies call for systematic study of TM n clusters on Gr sheet, to identify trends and classify the interactions between TM clusters and Gr.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation